Ejector Profile Modelling for Compressor-Driven Ejector Refrigeration System - Garcia, John Carlo S.; Alcaraz, Joselito Yam T.; Alvarez, Joseph Reymond T.; Abuan, Binoe E.; Berana, Menandro S. (Philippine Engineering Journal; Vol 35 No 2 (2014), 2021)
This paper provides a comprehensive description of the design of the ejector dimension based on the thermodynamic properties of the refrigerant without allowing the ejector to experience shock. A nozzle and a diffuser with converging-diverging sections are used to avoid formation of shock along the mixing section of the ejector. The analysis of the fluid flow within the system is assumed to be homogenous and one-dimensional. The program produced in this paper is used for determining the geometry of the ejector based on the input parameters in the system-evaporating and condensing temperature, evaporator mass flow rate, and entrainment ratio. This paper also presents the performance of different refrigerants used in the compressor-driven refrigeration system with the same input parameters. The program has produced corresponding ejector profile along with the pressure and velocity across the geometry for a certain set of input parameters. It is also found out that ammonia has the highest coefficient of performance (COP) among the refrigerants used in the study.  Keywords: Ejector, compressor, refrigeration, COP